Understanding the vaginal microbiome among women with different genotypes of human papillomavirus infection in remote Andaman islands - Rehnuma Parvez; Santhiya Vijayakumar; Alwin Vins; Sudha Ramaiah; Anand Anbarasu; Lipika Biswas; Nisha Beniwal; Harpreet Kaur; Nagarajan Muruganandam (Frontiers in Cellular and Infection Microbiology)
BackgroundHuman papillomavirus (HPV) is a viral infection, and its acquisition and persistence are significantly influenced by the vaginal microbiota. Understanding and comparing the vaginal microbiome of HPV infected women in Andaman and Nicobar Islands is crucial.MethodsThe study involved collecting vaginal swabs and extracting DNA using the QIAamp DNA Minikit. The DNA was then subjected to PCR amplification to confirm HPV infection. illumina NovaSeq 6000 platform was utilized to perform sequencing utilizing 2 x 250 paired end chemistry. Taxonomic analysis was performed and Bacterial abundance plots were generated and samples were grouped based on demographic parameters, pap test diagnosis, and genotypes. To assess diversity, samples were rarefied to 49,000 sequence reads per sample, and alpha and beta diversity metrics were calculated.ResultsThe study analyzed the presence of 21 assigned phyla, with Firmicutes, Actinobacteria, Bacteriodetes, and Proteobacteria emerging as the predominant taxa. At the genus level, Lactobacillus and Gardnerella dominated across all samples. Gardnerella was significantly more abundant in HPV-positive (22.40%) compared to HPV-negative samples (10.04%). Symptomatic group of HPV-positive samples had Gardnerella, and unclassified Coriobacteriaceae being dominant. In terms of bacterial diversity, the study found statistically significant association when comprising individuals aged 21 to 30 years to those aged 31 to 40 years.ConclusionMost research concluded that exposure to HPV can boost bacterial diversity in vagina compared to healthy women, increasing the risk of cervical cancer development. Current study highlights the importance of vaginal microbiome associated with high and low risk HPV, various age group as well as the symptomatic and asymptomatic cases of HPV infected women in South Andaman.